IMPLEMENTASI DATA MINING DENGAN METODE REGRESI LINEAR BERGANDA UNTUK MEMPREDIKSI DATA PERSEDIAAN BUKU PADA PT. YUDHISTIRA GHALIA INDONESIA AREA SUMATERA UTARA - Indah Lestari Lumban Gaol; Sinar Sinurat; Edward Robinson Siagian (STMIK Budi Darma, 2019)
PT. Yudhistira Ghalia North Sumatra. Where Inventory (stock) of goods is an important thing in a company for data collection or checking activities in order to find out the amount of goods that are used up and goods that will be needed in a company. Inventory of goods is always needed in company activities. So that in the supply of books has been delayed for making stock and excess stock making of books. In this study, multiple linear regression method will be used to predict book inventory data. So for that we need to predict book inventory data for the future how many books should be in stock. Multiple linear regression algorithm has advantages such as generalizing and extracting from certain data patterns, being able to acquire knowledge even though there is no certainty, and being able to do calculations in parallel so that the process is shorter. After being predicted, it will be possible to produce results that can be used in the future so that it can help PT. Yudhistira especially the part of the inventory of goods which must be provided in the following month.Keywords: Data Mining, Inventory, Multiple Linear Regression Algorithms